Rancangan dan Pengujian Perangkat Lunak Menggunakan Web Service pada Sistem Informasi Akademik - Ceria Asa Malinda; Sandy Kosasi (SISFOTENIKA, 2020)
The author conducted a study of the need to process and integrate data at High School with systems that already exist so that these systems can communicate unhindered difference platform and programming language used. Therefore, the author makes an Academic Information System software Using Web Services in order to connect the Academic Information System with the Financial Administration Information System. Forms of research by the author is the study of literature with data collection techniques of observation, interviews, and documentation. The method used is a Research and Development (R & D), whereas software design methods using Extreme Programming (XP) by implementing 4 practical way XP development, i.e, planning, design, coding, and testing. The results of this in the form of software design Academic Information Systems, Information Systems of Financial Administration, and Web Service. Academic Information System software using Sublime Text 2 application with PHP programming language, software Financial Administration Information System platform using Visual Studio 2012 with Visual Basic.NET programming language and web services created using ASP.NET Web Form Application with the programming language Visual Basic.NET and publish it by using the Internet Information Services (IIS) version 7.5.